Correlation of renal complications with extent and progression of tissue damage in electrical burns - D. C. Chauhan; P. S. Chari; G. K. Khuller; Dalbir Singh (Indian Journal of Plastic Surgery)
Electrical injuries due to high-tension voltage (>1000 volts) cause destruction at the point of contact with massive necrosis of deeper structures such as muscles, vessels and nerves. Rhabdomyolysis due to massive breakdown of skeletal muscles may lead to acute renal failure secondary to myoglobinuria. The study was undertaken to observe the correlation of renal complications with extent and progression of tissue damage in high-tension voltage electrical burns. Renal biochemical parameters as predictors of acute renal failure were also studied. Thirty two patients of high tension voltage electrical burn injuries presenting during one year period 1-1-2001 to 31-12-2001 were studied. Low-tension voltage electrical injuries (< 1000 volts) mimic thermal burns were excluded from the study. The electrical wound assessment and the renal biochemical parameters were done daily for the first seven days and then on alternate days for another seven days. Assessment of progression of wounds and correlation with the renal biochemical parameters was done. Patients who died following electrical burns were subjected to autopsy and histopathological examination of both kidneys. Out of the thirty-two patients, six (18.75%) went into acute renal failure. Five out of these six patients died because of renal failure (mortality rate 83.33%). There was definite progression of electric burn wounds. There was no correlation between progression of electrical burn wounds and acute renal failure. Serum creatinine was found to be the most important biochemical parameter as a prognostic indicator of acute renal failure.